A social constructivism framing of mobile pedagogy in english language teaching in the digital era - Zhang Jie; Marlia Puteh; Abu Hasan Sazalli (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Social Constructivism is elaborated as a theoretical background to support modern pedagogy with mobile technology in the digital age. Studies of theories and framework in terms of mobile pedagogy are combed up to find its connection between language teaching and Social Constructivism. Four theoretical framework of mobile pedagogy are listed in this paper to establish the link with Social Constructivism. The analysis of the Zone of Proximal Development from Social Constructivism theory indicates that mobile pedagogy, integrated with technology, pedagogy and subject content, is student-driven model which needs teacher’s guidance in the level that students cannot scaffold knowledge on their own. Teachers have to update pedagogical concept with enhanced technological knowledge for the demand of education in the digital era.